2008
DOI: 10.1111/j.1750-3841.2008.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Novel Hydroxypropyl Methylcellulose Films Containing Chitosan Nanoparticles

Abstract: In this study, chitosan nanoparticles were prepared and incorporated in hydroxypropyl methylcellulose (HPMC) films under different conditions. Mechanical properties, water vapor and oxygen permeability, water solubility, and scanning and transmission electron microscopy (SEM and TEM) results were analyzed. Incorporation of chitosan nanoparticles in the films improved their mechanical properties significantly, while also improving film barrier properties significantly. The chitosan poly(methacrylic acid) (CS-PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 26 publications
5
46
0
Order By: Relevance
“…In the case of general food packaging, water insolubility is expected for the packaging materials [25]. Water solubility index (WSI) of the films is shown in Table 1.…”
Section: Water Solubility Indexmentioning
confidence: 99%
“…In the case of general food packaging, water insolubility is expected for the packaging materials [25]. Water solubility index (WSI) of the films is shown in Table 1.…”
Section: Water Solubility Indexmentioning
confidence: 99%
“…The pectin and HPMC films were obtained according to the procedure reported by Moura et al [2] The polysaccharide solution (control film) was obtained dissolving 3.0 g of polysaccharide in 100 mL of distilled water under magnetic stirring for 12 h. A 3.0 (% w:v) polysaccharide solution was used in all film formulations. The films based on nanocomposites were obtained by addition of 3.0 g of polysaccharide in 100 mL of clay solution (both freshly synthesized), under magnetic stirring for 12 h. After the solutions were prepared, the flasks were allowed to rest for 6 h to degas in order to prevent microbubble formation within the films.…”
Section: Nanocomposites Preparation By Castingmentioning
confidence: 99%
“…Numerous studies have been conducted investigating the properties of various protein, polysaccharide, and lipid-based biopolymer materials. Natural biopolymers have the advantage of being biodegradable, renewable, and often edible [2][3] . However, biopolymer films have exhibited relatively poor mechanical and water vapor barrier properties when compared to traditional polymeric films, therefore limiting their commercial use [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, when chitosan whiskers were added to chitosan films, it was observed that whiskers enhanced the tensile strength and water resistance of the chitosan films [98]. Chitosan nanoparticles can be prepared by ionic gelation [100] and it was found that incorporation of chitosan-tripolyphosphate nanoparticles in hydroxyproponyl methylcellulose increased the mechanical and barrier functions of the films [101].…”
Section: Chitosan Based Nanocompositesmentioning
confidence: 99%